2000
DOI: 10.1055/s-2000-8657
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Serine Proteases by Anti-Inflammatory Triterpenoids

Abstract: The lupane triterpenoid lupeol, the ursane triterpenoid alpha-amyrin and esters of these compounds are present in the bark of roots of Alstonia boonei (Apocynaceae) and have anti-inflammatory properties. alpha-Amyrin is a competitive inhibitor of bovine trypsin and chymotrypsin (Ki values 29 microM and 18 microM, respectively). Lupeol linoleate, lupeol palmitate and alpha-amyrin linoleate are non-competitive inhibitors of trypsin (Ki values 7 microM, 10 microM and 16 microM, respectively). alpha-Amyrin linolea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 8 publications
0
36
0
2
Order By: Relevance
“…Lupeol has been shown to possess strong anti-inflammatory, antiarthritic, antimutagenic and antimalarial activity in vitro and in vivo systems (Guevara et al, 1996;Geetha and Varalakshmi, 1999;Geetha and Varalakshmi, 2001;Ziegler et al, 2002). Lupeol has been shown to act as a potent inhibitor of protein kinases and serine proteases (Hasmeda et al, 1999;Rajic et al, 2000;Hodges et al, 2003) and inhibit the activity of DNA topoisomerase II, a target for anticancer chemotherapy (Moriarity et al, 1998;Wada et al, 2001). Lupeol has also been shown to improve the epidermal tissue reconstitution (Nikiema et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Lupeol has been shown to possess strong anti-inflammatory, antiarthritic, antimutagenic and antimalarial activity in vitro and in vivo systems (Guevara et al, 1996;Geetha and Varalakshmi, 1999;Geetha and Varalakshmi, 2001;Ziegler et al, 2002). Lupeol has been shown to act as a potent inhibitor of protein kinases and serine proteases (Hasmeda et al, 1999;Rajic et al, 2000;Hodges et al, 2003) and inhibit the activity of DNA topoisomerase II, a target for anticancer chemotherapy (Moriarity et al, 1998;Wada et al, 2001). Lupeol has also been shown to improve the epidermal tissue reconstitution (Nikiema et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…1), a triterpene found in fruits (such as olive, mango, strawberry, grapes, and figs), in many vegetables, and in several medicinal plants, is used in the treatment of various aliments worldwide by native people (18)(19)(20). Lupeol possesses strong antioxidant, anti-inflammatory, antiarthritic, antimutagenic, and antimalarial activity in vitro and in vivo systems; acts as a potent inhibitor of protein kinases and serine proteases; and inhibits the activity of DNA topoisomerase II, a target for anticancer chemotherapy (21)(22)(23)(24)(25)(26)(27). It has also been shown that Lupeol induces differentiation and inhibits the cell growth of mouse melanoma and human leukemia cells (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…24 It has been reported that A scholaris bark contains the alkaloids alstonidine, alstonin, alstovenine, chlorogenic acid, chlorogenine, ditain, ditaine, echicaoutchin, echicerin, echiretin, echitamine, echaitein, echitinin, echitin, porphyrine, porphyrosine, and reserpine. 5,25,26 Antioxidants act synergistically to counteract the deleterious effects of free radical-mediated LPO. SOD and CAT protect cells by catalyzing the harmful ROS such as O 2 -(SOD) and H 2 O 2 (CAT).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Epidemiological studies have indicated that the risk of cancer may be modified by changes in dietary habits. 5 Humans ingest a large number of naturally occurring antimutagens and anticarcinogens in food, which may inhibit one or more stages of carcinogenesis. 3 Several studies have indicated that compounds with antioxidants or anti-inflammatory properties as well as certain phytochemicals can inhibit tumor initiation, promotion, and progression in experimental animal models.…”
Section: Introductionmentioning
confidence: 99%